2021
DOI: 10.34172/aim.2021.22
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab and Intravenous Gammaglobulin in Hospitalized Severe COVID-19 Patients in Intensive Care Unit

Abstract: Background: Severe coronavirus disease 2019 (COVID-19) may lead to the cytokine storm syndrome which may cause acute respiratory failure syndrome and death. Our aim was to investigate the therapeutic effects of infliximab, intravenous gammaglobulin (IVIg) or combination therapy in patients with severe COVID-19 disease admitted to the intensive care unit (ICU). Methods: In this observational research, we studied 104 intubated adult patients with severe COVID-19 infection (based on clinical symptoms, and radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Other biologic immunomodulators may be considered in severe cases with no response to anakinra. Infliximab and tocilizumab, used in other hyper-inflammatory syndromes as biologic immunomodulators have been tried to modulate the dysregulated hyper-inflammation apparent in MIS-C with promised result in adults [ 20 , 21 ]. However, there is limited evidence to suggest these therapies in children.…”
Section: Discussionmentioning
confidence: 99%
“…Other biologic immunomodulators may be considered in severe cases with no response to anakinra. Infliximab and tocilizumab, used in other hyper-inflammatory syndromes as biologic immunomodulators have been tried to modulate the dysregulated hyper-inflammation apparent in MIS-C with promised result in adults [ 20 , 21 ]. However, there is limited evidence to suggest these therapies in children.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we also found that the duration of hospitalization in the medium dose subgroup of IVIG was longer than control group and no positive effects were obtained on duration of mechanical ventilation and mortality of patients. Many studies have shown that IVIG administration reduces mortality in patients with COVID-19, but increases hospitalization time instead of standard COVID-19 treatment [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The source of IVIG was not detailed (i.e., pre-or post-pandemic), and no data were provided on the presence of neutralizing or other anti-SARS-CoV-2 antibody. The benefits of IVIG are debatable, but several studies have not determined the pre-existing antiviral potency of the same [191][192][193][194][195]. Such studies do not preclude the potential benefit of IVIG in other niche situations, such as immune thrombocytopenia, ascending polyneuropathy, or multisystem inflammatory disorder attributable to COVID-19 [196][197][198].…”
Section: Human Trials Of Passive Immunitymentioning
confidence: 99%